A new yellow species of glassfrog (Centrolenidae: Nymphargus) from the Amazonian slopes of the Ecuadorian Andes - Guayasamin, Juan M. (Zootaxa, 2013)
I describe a new glassfrog from the cloud forest of the Andes of southwestern Ecuador (Plan de Milagro–Gualaceo road; 3.0077°S, 78.53318°W), at elevations between 2140–2160 m. The new species is distinguished mostly by having a pale yellow dorsal coloration instead of the green that characterizes most centrolenids. Morphological traits (i.e., reduced web-bing between Fingers III and IV and lack of humeral spines) support the placement of the new species in the genus Nymph-argus.